PENERAPAN DOODLING MOTIF RAGAM HIAS PADA HEWAN ENDEMIK YANG TERDAPAT DI RELIEF CANDI BOROBUDUR MELALUI ACTIVITY BOOK UNTUK ANAK USIA 14-25 TAHUN - Khoirul Badri, Ahmad; Rakhman, Rizki Taufik (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2024)
The aim of this research is to uniquely introduce the decorative motifs and endemic animals of Borobudur Temple (as a cultural heritage site and super-priority destination) through a doodling activity book, specifically targeting the 14–25 age group. The method used is a qualitative approach with a design thinking framework. Data collection was conducted through questionnaires, interviews, observations, and product trials involving potential users. The research process included the identification of relief motifs (1,460 carvings) and endemic animals at Borobudur Temple, as well as the design of a doodling activity book based on data from questionnaires and interviews. Expert validation was carried out by a language expert, an activity book design expert, and the Ministry of Tourism and Creative Economy (as the policy holder of the super-priority destination). Product trials with respondents aged 14–25 resulted in positive responses. The outcome of the research is a tested and validated doodling activity book that serves as an interactive medium to introduce the visual richness of Borobudur Temple.